2011
DOI: 10.2217/bmm.11.71
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Epilepsy Biomarkers in the Immature Brain: Goals, Challenges and Strategies

Abstract: Epilepsy and seizures are very common in the early years of life and are often associated with significant morbidity and mortality. Identification of biomarkers for the early detection of epileptogenicity, epileptogenesis, comorbidities, disease progression and treatment implementation will be very important in implementing more effective therapies. This article summarizes the current needs in the search for new early life epilepsy-related biomarkers and discusses the candidate biomarkers that are under invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 87 publications
(91 reference statements)
0
42
0
Order By: Relevance
“…In addition, the future serial EEGs obtained as part of FEBSTAT along with MRIs and clinical follow-up may serve as biomarkers for the development of epilepsy. [26][27][28] …”
Section: -24mentioning
confidence: 99%
“…In addition, the future serial EEGs obtained as part of FEBSTAT along with MRIs and clinical follow-up may serve as biomarkers for the development of epilepsy. [26][27][28] …”
Section: -24mentioning
confidence: 99%
“…Past early-identification of DRE is mainly based on clinical manifestations like the number of seizures [19]. Other than applying the well-established electroencephalography (EEG) monitoring, other imaging testsing and clinical symptoms and signs watching, DRE urgently requires a set of molecular biomarkers to clarify the early prognosis, wherein microRNAs play an important role [20][21][22].…”
Section: Drug-resistant Epilepsy: Definition and Prognosismentioning
confidence: 99%
“…Similar to miRNA in tumorigenesis, miRNAs exhibit a dual role in epileptogenesis-neuroprotection or induce neural cell death. A large number of studies have shown that the occurrence of epilepsy with nerve cells apoptosis, Synaptic connections reconstruction, glial fibers cell hyperplasia, abnormal pathways is closely related to the formation and inflammatory response [20,21]. Repeated seizures can result in hippocampus neuron apoptosis in brain, the abnormal formation excitatory synapses loop, and ultimately improve the intractable temporal lobe epilepsy [23,24].…”
Section: Pathogenetic Mechanisms Of Mirna-mediated Epileptogenesismentioning
confidence: 99%
“…However, across-species comparisons of brain growth, DNA, cholesterol, and water content suggested that PN8 -10 rats are more closely related to full-term human newborns (Gottlieb et al 1977;Dobbing and Sands 1979), although eye opening does not occur until PN13 -15 and rodent pups are able to ambulate and run during the third week of life, unlike most infants. In reality, different developmental processes mature at different tempos across species, making definite equivalency rules difficult to generalize (Avishai-Eliner et al 2002;Galanopoulou and Moshé 2011). In this review, we will mostly refer to models that show epilepsy during the first 3 wk of life (thought of as equivalent to neonatal and infantile age) or have been constructed with the intent to recreate human neonatal and infantile epilepsies.…”
Section: Developmental Equivalency Across Speciesmentioning
confidence: 99%